New classifications of axillary lymph nodes and their anatomical-clinical correlations in breast surgery - Roberto Cirocchi; Maria Ida Amabile; Alessandro De Luca; Federico Frusone; Domenico Tripodi; Patrizia Gentile; Renata Tabola; Daniele Pironi; Flavio Forte; Massimo Monti; Vito D’Andrea; Salvatore Sorrenti (World Journal of Surgical Oncology, 2021)
Abstract Background In the last decade, two research groups, the French group by Clough et al. (Br J Surg. 97:1659–65, 2010) and the Chinese one by Li et al. (ISRN Oncol 2013:279013, 2013), proposed two types of classification of axillary lymph nodes in breast cancer, identifying novel anatomic landmarks for dividing the axillary space in lymph node dissection. Main body Knowledge of the exact location of the sentinel node helps to focus the surgical dissection and to reduce the morbidity of sentinel lymph node biopsy procedures, in particular the risk of arm lymphedema, without compromising sensitivity. Conclusion In this article, we aimed at focusing on the clinical impact that the most recent classifications of axillary lymph nodes have obtained in literature, highlighting the importance of defining new demarcations to preserve the axillary lymph nodes as much as possible in breast surgery.